Influence of beryllium addition on the microstructural evolution and mechanical properties of Zr alloys. (January 2015) - Feng, Z.H.; Jiang, X.J.; Zhou, Y.K.; Xia, C.Q.; Liang, S.X.; Jing, R.; Zhang, X.Y.; Ma, M.Z.; Liu, R.P.
Highlights: The content of Be2 Zr increases with the increase of Be. With the increasing Be, the shapes of original β grain boundaries transformed. The addition of Be plays a crucial role on the change of grain size. The tensile properties are improved with decreasing grain size. Abstract: The microstructural evolution and mechanical properties of Zr– χ Be binary alloys with different contents of Be ( χ  = 0, 0.25, 0.50, 0.75 and 1.00 wt.%) were studied in this paper. X-ray diffraction results showed that the phase composition of alloys underwent a series of changes from α phase to α phase + Be2 Zr after Be addition. Moreover, the content of Be2 Zr increased with increased Be. Microscopic analysis showed that the shape of prior-β grains gradually transformed from inerratic planar crystallization to cellular crystal and then irregular arborization. In addition, it would have an obvious effect on grain refinement with Be added. The average prior-β grain size in the pure Zr exceeded 1000 μm. The addition of 0.25 wt.% Be dramatically decreased the average size of prior-β grain to 170 μm. With the beryllium further increased gradually to 1.00 wt.%, the average size of prior-β grain in Zr– χ Be ( χ  = 0.50, 0.75, 1.00 wt.%) decreased gradually to 26 μm. The key factor affecting significant refinement is the enhancement in nucleation rate and the growth restriction factor values of Zr alloys resulting from Be addition. The microstructural variation of Zr–Be alloys with Be greatly affected mechanical properties. In this paper, the tensile strength of pure Zr was only approximately 560 MPa, and the ductility remained above 14%. In the Zr-based alloys, adding Be element is beneficial to the improvement of the tensile properties. Zr– χ Be ( χ  = 1.00 wt.%) possessed the highest tensile strength ( σ b  = 848 MPa) and retained an elongation of 8.6%. Scanning electro microscope results indicated that the fracture modes of Zr alloys with gradually added Be changed from ductile fracture to brittle fracture.